Analysis of the Effect of Paint Adhesion and Hardness on the Car Body Painting Process by Varying the Percentage of Paint Mixture - Nevada J.M Nanulaitta; Graciadiana I Huka; F Demmatacco; Berthy Pelasula (Journal Mechanical Engineering, 2025)
This study aims to analyze the effect of varying paint and thinner mixtures and the number of coats applied on the adhesion and hardness of car paint. The research method used was experimental, varying the paint:thinner ratio (100:110, 100:120, 100:130, and 100:140) and the number of coats applied (2 and 3). Adhesion testing was performed using a Cross-Cut Adhesion Tester, while hardness testing was performed using a Shore D Durometer. The results showed that a paint:thinner ratio of 100:130 provided optimal results for both tested parameters. In the adhesion test, the 100:130 ratio achieved level 5B (best) with no paint peeling, while in the hardness test, it reached the highest value of 88.77 HD. Excessive addition of thinner (ratio 100:140) resulted in a decrease in quality, with adhesion decreasing to level 3B and hardness dropping to 83.3 HD. Variations in the number of coats showed that using two coats provided more consistent results than three coats, especially in terms of adhesion. This study concluded that an optimal balance between paint and thinner is crucial for achieving good paint quality, with a 100:130 ratio providing the best results for automotive body painting applications. Keywords: Automotive Body Painting, Paint Adhesion, Paint Hardness, Paint-Thinner Mixture Variations, Paint Coating